2011
DOI: 10.1099/jmm.0.028654-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutant-prevention concentration and mechanism of resistance in clinical isolates and enrofloxacin/marbofloxacin-selected mutants of Escherichia coli of canine origin

Abstract: The antibacterial activity and selection of resistant bacteria, along with mechanisms of fluoroquinolone resistance, were investigated by integrating the static [MIC or mutant-prevention concentration (MPC)] and in vitro dynamic model approaches using Escherichia coli isolates from diseased dogs. Using the dynamic models, selected E. coli strains and enrofloxacin and marbofloxacin at a range of simulated area under concentration-time curve over a 24 h interval (AUC 24 h )/MIC ratios were investigated. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 37 publications
9
36
0
6
Order By: Relevance
“…In the present study, AUC/MPC ratios to reduce Salmonella-resistant mutants were 69 (DIF), 62 (ENR), and 39 (MAR). These results were consistent with previous reports (22,24). However, in the current study, no difference of potency was found through conversion from AUC/MIC ratios to AUC/MPC ratios resulting from different MPC/MIC ratios, because the MPCs of all 3 FQs were 4 times higher than their respective MICs.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In the present study, AUC/MPC ratios to reduce Salmonella-resistant mutants were 69 (DIF), 62 (ENR), and 39 (MAR). These results were consistent with previous reports (22,24). However, in the current study, no difference of potency was found through conversion from AUC/MIC ratios to AUC/MPC ratios resulting from different MPC/MIC ratios, because the MPCs of all 3 FQs were 4 times higher than their respective MICs.…”
Section: Discussionsupporting
confidence: 83%
“…This was in agreement with our previous findings using FQs against E. coli and Actinobacillus pleuropneumoniae (16,22,24). Furthermore, the I E showed species specificity that was lower (8 to 41%) than those from reports using non-biofilm-forming bacteria, while it was similar to I E s of FQs against biofilm-forming bacteria (difference of 8 to 10%) (16,22,24). The failure of FQs to suppress Salmonella growth in the culture could result not only from resistant populations but also from biofilm formation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations